2022
DOI: 10.15587/1729-4061.2022.265781
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of amplitude spectra of the third order for the early detection of indoor fires

Abstract: The object of this study is the dynamics of hazardous parameters of the gas environment during the ignition of materials. The problem that was solved is the early detection of fires in the premises. The research results indicate the nonlinear nature of the dynamics of hazardous parameters of the gas environment in the absence and presence of materials ignition. It was established that the bispectrum amplitude, in contrast to the amplitude spectrum of the hazardous parameters of the gas medium, contains informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Thus, measure (3) allows us to study the features of the sample coefficient of variation of the DP of the GE at characteristic intervals of the absence and appearance of F of materials in the laboratory chamber. Results in Table 1 do not contradict known data [21,44,45].…”
Section: Discussion Of Results Of the Study Of Sample Coefficients Of...mentioning
confidence: 47%
See 3 more Smart Citations
“…Thus, measure (3) allows us to study the features of the sample coefficient of variation of the DP of the GE at characteristic intervals of the absence and appearance of F of materials in the laboratory chamber. Results in Table 1 do not contradict known data [21,44,45].…”
Section: Discussion Of Results Of the Study Of Sample Coefficients Of...mentioning
confidence: 47%
“…However, moments of the third and fourth order, which make it possible to identify nonlinear relationships, as well as their specific variations, are not studied. Features of the third-order amplitude spectra of DP GE are studied in [21]. It has been established that third-order amplitude spectra allow EO based on the nonlinear relationship between the frequency components in the spectrum.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…Features of the spectra of changes in hazardous parameters of GE of the order above the second, capable of detecting nonlinearity, are not investigated. Paper [38] investigates the features of amplitude spectra for hazardous GE parameters in a laboratory chamber. At the same time, it is shown that third-order amplitude spectra make it possible to identify nonlinear relationships of frequency components in the spectrum of change in hazardous GE parameters.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%